The Effects of Mass Trials versus Distributed Trials During a Shared Story Reading for Students with Moderate to Severe Disabilities - Nasir-Tucktuck, Mona; Baker, Joshua N.; More, Cori; Wennerlind, K. Ryan; Devine, Stephanie M. (Journal of the American Academy of Special Education Professionals, 2020)
This study used a single-subject alternating treatment design across students to compare mass discrete trials and distributed mass trials distributed in a shared story reading on the acquisition of functional skills for students with Autism. The results of this study examined a functional relationship between the interventions on the acquisition of skills and decrease in interfering behaviors. Two early childhood students in a self-contained classroom were the participants for the study. The results of the study indicated that both instructional strategies were effective in supporting the acquisition of the target skills. However, the interfering behaviors of the two students were different in both instructional settings. The results suggest that students were able to generalize better using the distributed trials. Also, using the shared story reading allowed the students to access the general education literacy curriculum and exposed the students to emergent literacy skills that are typically taught to their peers in the general education classes. Results and conclusions are discussed in terms of future research and implications for including children with moderate and severe disabilities in general education classes.